The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1107/s2052252518017037
|View full text |Cite
|
Sign up to set email alerts
|

Origin of chromic effects and crystal-to-crystal phase transition in the polymorphs of tyraminium violurate

Abstract: Chromic materials are nowadays widely used in various technological applications, however understanding the effect and the possibility of tuning the obtained colour of a material are still challenging. Here a combined experimental and theoretical study is presented on the solvatochromic and crystallochromic effects in the (pseudo)polymorphs of tyraminium violurate. This organic material exhibits a large solvatochromic shift (ca 192 nm) associated with broad colour change (from yellow to dark violet). Tyraminum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 49 publications
(45 reference statements)
0
15
1
Order By: Relevance
“…Previously, some of us have shown experimentally that co‐crystallization affects the thermo‐ and photochromic behaviors of N‐salicylideneanilines (or anils), depending on the coformer (the secondary compound) . Anils are dynamical compounds, whose color changes when triggered by external stimuli . They are able to switch between an enol (E) and a keto (K) form and each ought to be affected differently by the coformer.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, some of us have shown experimentally that co‐crystallization affects the thermo‐ and photochromic behaviors of N‐salicylideneanilines (or anils), depending on the coformer (the secondary compound) . Anils are dynamical compounds, whose color changes when triggered by external stimuli . They are able to switch between an enol (E) and a keto (K) form and each ought to be affected differently by the coformer.…”
Section: Introductionmentioning
confidence: 99%
“…A series of co-crystals of sulfamethoxazole [241] and leflunomide [242] were synthesized using this approach. Prediction of possible H-bonded motifs between tyraminium cations and violurate anions also successfully predicted many of the bimolecular synthons experimentally observed in tyraminium violurate polymorphs and hydrates, but also demonstrated that none of the trimolecular synthons were predicted [243]. Note, that tri-and tetra-molecular synthons are not something unusual in co-crystals (see, for example, tetramolecular associates found in thiazole-amides, Figure 10), thus any predictions should also include such polymolecular associates into account.…”
Section: Co-crystals Designmentioning
confidence: 71%
“…The itraconazole lacks any donors of strong H-donors but has a number of competing acceptors of H- This tool has been applied mainly for the analysis of strong hydrogen bonds [54,170,190,194,[248][249][250][251] in accord with the first test functional groups suggested within this tool, and the first paper published to describe it. Mutual disposition of hot spots can be used to find functional groups of the same molecule [245], co-formers [243,249,250], active sites in a binding pocket of a macromolecule [252], or surface inhibitors [170], which match a given pattern of interaction preferences. Analysis of polymorphs of some drugs demonstrated that disposition of H-bond donors and acceptors close to the hotspots are indicative for the more stable polymorph even if a molecule realizes less likely conformation [190].…”
Section: Full Interaction Mapsmentioning
confidence: 99%
“…Crystal‐to‐crystal phase transformation is an interesting phenomenon with potential applications in molecular devices such as switches and sensors [56] . The structural transformations typically involve minute movements of atoms in a crystal caused by changes in the coordination number of metals, [57] condensation reactions, rearrangement of bonds, [56, 58] or removal or exchange of solvents [59] . They are often accompanied by changes in properties such as magnetism, [56] conductivity, [60] luminescence, [61] etc.…”
Section: Introductionmentioning
confidence: 99%